Agriculture and climate change: The role of nutrient management in mitigation - Flynn, Helen C. (International Food Policy Research Institute, 2009)
Nitrous oxide (N2O) emissions from soils are responsible for about 3 percent of greenhouse gas (GHG) emissions, which cause climate change, and contribute approximately one-third of non-CO2 agricultural GHG emissions. N2O is produced by microbial transformations of nitrogen in the soil, under both aerobic and anaerobic conditions. Therefore, emissions are often directly related to nutrients added to the soil in the form of mineral fertilizers and animal manure. These additions can be vital in maintaining soil fertility and crop production; about half of the world’s population is dependent on food produced strictly because of mineral fertilizer inputs. However, the additions are also highly inefficient, leading to nitrogen losses via leaching, volatilization, and emissions to the atmosphere. By helping to maximize crop-nitrogen uptake, improved nutrient management has a significant and cost-effective role to play in mitigating GHG emissions from agriculture. Nutrient management can also help reduce methane (CH4) emissions from rice production and increase carbon sequestration in agricultural soils.